Ursodeoxycholic Acid Alters Bile Acid and Fatty Acid Profiles in a Mouse Model of Diet-Induced Obesity - Zhang, Yunjing; Zheng, Xiaojiao; Huang, Fengjie; Zhao, Aihua; Ge, Kun; Zhao, Qing; Jia, Wei (Frontiers in Pharmacology, 2019)
Ursodeoxycholic acid (UDCA) is a bile acid (BA) approved by the U.S. Food and Drug Administration for the treatment of primary biliary cholangitis. It is also the major active component of bear bile used in traditional Chinese medicine to reduce fever, remove toxins, and treat liver and eye ailments. In addition, UDCA and its conjugated form have been evaluated for their potential to improve symptoms of metabolic diseases, but the results have been inconclusive. To address this issue, in this study we investigated the effects of orally administered UDCA on mice with diet-induced obesity, including the BA and free fatty acid (FFA) profiles of serum, liver, and epididymis and brown adipose tissues. We found that UDCA treatment significantly improved most metabolic indices; tauroursodeoxycholic acid (TUDCA) and taurolithocholic acid (TLCA) contents were increased in all examined tissues, whereas saturated FA levels were decreased and n-3 polyunsaturated fatty acid (n-3 PUFA) levels were increased in most tissues. A correlation analysis showed that the concentrations of UDCA and its derivatives were positively correlated with that of n-3 PUFA. To clarify the mechanism by which UDCA alters FFA profiles, we analyzed the expression levels of genes involved in FFA biosynthesis, uptake, and oxidation and found that FFA biosynthesis and uptake were inhibited while FFA oxidation was stimulated by UDCA treatment. Additionally, amino acid-conjugated derivatives of UDCA, such as TUDCA and TLCA, altered FFA profiles by modulating FFA biosynthesis, uptake, and oxidation. These findings provide evidence that UDCA can alleviate metabolic dysfunction and could therefore be effective in the treatment of obesity.